Kontrastif Konjungsi Transisi Namun dan Tetapi Dalam Bahasa Indonesia Dan Que dan Bu Guo dalam Bahasa Mandarin - Paulia, Paulia; Hualangi, Cynthia Hualangi; Sugiroto, Ng (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This research aims to use contrastive analysis on the contradictory conjunctions found in Indonesian and Mandarin languages, by comparing the word “namun” with “ ?? bùguò” and the word “tetapi” with “ ? què”. This research employs a qualitative descriptive approach to analyze and observe the similarities and differences of contradictory conjunctions in Indonesian and Mandarin languages based on the contrastive theory in the field of linguistics. The data collection technique used is documentation, both digital and non-digital, which includes three Indonesian books and three Mandarin books. The results of this research show that in the contradictory conjunctions “tetapi” and “què”, there are 11 similarities and 4 differences, while in the conjunctions “namun” and “bùguò”, there are 12 similarities and 8 differences.